Diseases (Springhouse Corporation, 1997)
Covers more than 530 diseases, including emerging diseases such as Ebola virus. For each disorder, readers learn the causes, complications, assessment findings, tests, treatments, and interventions. Also included are NANDA-approved nursing diagnoses, DSM-IV criteria, revised classification system for HIV infection, peptic ulcer causes and treatment, the latest findings in immunology, and much more. Chapter introductions cover such topics as disease transmission and prevention, anatomy and physiology, assessment, and diagnostic tests. Critical warnings, assessment tips, and home care information are highlighted. Nurses also find sample plans of care, plus over 500 clear photographs, illustrations, and charts that show the visible effects of diseases, clarify pathophysiology, compare disease types and characteristics, and mor